Investigating the Differences between the Components of Meta-Emotions and Mindfulness in Depressed and Normal People - Mohsen Mohajeri; Aniseh Alfooneh; Afsaneh Karbasi (International Journal of Body, Mind and Culture, 2023)
Background: Depression is one of the most serious threats to today's society and of course, one of the most common psychological disorders. This research aims to investigate the differences between the components of meta-emotions and mindfulness in people with depression and normal people.